The relationship between the lack of training in communication skills and the use of defensive medicine in Mexico and Per - Cruz Donayre, Claudia Victoria (2024)
The communication between doctor and patient is highly relevant as it can influence patients’ health outcomes, their adoption of treatment, their decision to continue or discontinue it, and their satisfaction with the care provided by physicians. On the other hand, defensive medicine encompasses medical attention that does not increase patient benefits and results in the overuse of medical services, driven by the physician’s fear of being sanctioned and/or preventing litigation risks. This research aimed to explore the relationship between the lack of training in communication skills among physicians and defensive medicine. The design was non-experimental, correlational; using a logical deductive method and a quantitative approach. The population studied consisted of physicians from Mexico and Peru, with a sample of 350 professionals (175 from each country). It reaffirmed the importance of training in communication skills for physicians; however, it was evident that a high percentage did not receive such training or received it in a very basic manner. Their behaviors indicated the practice of defensive medicine (although not all were familiar with the concept) and suggested that better communication training could influence a change in attitude.